Дипломатичні архіви Білоруської Народної Республіки 1918–1921 років як джерело вивчення білорусько-польських та білорусько-українських відносин - Міхалюк, Д. (Спеціальні історичні дисципліни: питання теорії та методики, 2017)
Статтю присвячено збереженим документам дипломатичних інституцій Білоруської Народної Республіки та оцінці їх джерельного значення для дослідження білорусько-українських та білорусько-польських стосунків. В статті окреслено основні цілі Білоруської Народної Республіки на міжнародній арені та творення консульської служби. Здійснено огляд джерел, що зберігаються в Національному архіві Республіки Білорусь, Литовському центральному історичному архіві, центральному державному архіві вищих органів влади та управління України, Архіві нових документів у Варшаві, Державному архіві Російської Федерації та інших архівах. Авторка також звертає увагу на знищені архіви та пропонує нові дослідницькі підходи з використання опосередкованих джерел. The main aim of the article is to characterise the historical sources of the diplomatic institutions of the Belarusian National Republic and the assessment of theirs usefulness to the research of the Belarusian-Polish- and Belarusian-Ukrainian relations in 1918–1921. Only a few archives of diplomatic institutions of the BNR could survive. In the article the main goals of the BNR on international agenda and the way of organisation of consular missions were described. The author informs about the documents collected in the National Archive of the Belarusian Republic in Minsk, in Lithuanian Central Historical Archive in Vilnius, in the Central State Archives of Supreme Bodies of Power and Government of Ukraine, the Archive of New Records in Warsaw, in the State Archive of the Russian Federation and the others. The author informs also about the missing collections and proposes the directions of research based on the indirect sources.